PERTUMBUHAN EKSPLAN MANGGIS (Garcinia mangostana L.) SECARA IN VITRO DENGAN AIR KELAPA, EKSTRAK TAUGE DAN RAGI - sarah, May; Wulandari, Reine Suci; Darwati, Herlina (Universitas Tanjungpura, 2013)
Garcinia mangostana L. is a species tropical forest that has many benefit. The benefit mangosteen for human life makes it worth as commodity in International market. This aimed to find out the influence of coconut water, tauge extract, and yeast for mangosteen explants growth. The research took place in Sylviculture Laboratory at Tanjungpura University for 2 month. The data analyzed to use Non Parametric Statistics. The are four treatments given those are T0 = Control, T1 = Coconut water 15%, T2 = Tauge extract 15% and T3 = Yeast 8% with 7 repplications so there are 28 explants. For the whole, the parameters observed were the first times callus and sproud appear, the counts of explants had callus, sproud, browning or constant and the percentation of explants growth. Kruskal Wallis showed that the treatments didnt influence the growth of mangosteen explants. But, Chi-Square analysis showed that it gave influence for the value of mangosteen sproud explants. Yeast had 4 explants which make mangosteen explant sprouted. Its high and low value of sproud are 4 and 10. Base on it, yeast give a good influence for the mangosteen explants in vitro. Keywords : Mangosteen Explants, Coconut Water, Tauge Extract, Yeast, budidaya manggis